Road for understanding cancer stem cells: model cell lines - ERZİK, CAN (FUTURE MEDICINE LTD, 2007)
There is increasing evidence suggesting that stem cells are susceptive to carcinogenesis and, consequently, can be the origin of many cancers. Recently, the neoplastic potential of stem cells has been supported by many groups showing the existence of subpopulations with stem cell characteristics in tumor biopsies such as brain and breast. Evidence supporting the cancer stem cell hypothesis has gained impact due to progress in stem cell biology and development of new models to validate the self-renewal potential of stem cells. Recent evidence on the possible identification of cancer stem cells may offer an opportunity to use these cells as future therapeutic targets. Therefore, model systems in this field have become very important and useful. This review will focus on the state of knowledge on cancer stem cell research, including cell line models for cancer stem cells. The latter will, as models, help us both in the identification and characterization of cancer stem cells and in the further development of therapeutic strategies including tissue engineering.
Keywords: cancer stem cells; model lines; stem cells; MAMMARY EPITHELIAL-CELLS; SELF-RENEWAL; BREAST-CANCER; BRAIN-TUMORS; INITIATING CELLS; SONIC-HEDGEHOG; ENDOTHELIAL-CELLS; CARCINOMA-CELLS; DOWN-REGULATION; GASTRIC-CANCER